Improving Healthy Behavior in Preventing Stunting through Digital Media - Aris Tyarini, Indrawati; Setiawati, Ari; Septiyana Achmad, Viyan; Astuti, Astuti (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Stunting is a global health problem that affects children's physical growth and cognitive development. The presence of digital media has become an integral part of everyday life, and its utilization as a tool to promote healthy behaviors in preventing stunting offers significant potential. This dedication aims to explain the role of digital media in improving healthy behavior in preventing stunting. The method used is a comprehensive literature review of recent studies that discuss the use of digital media to influence public behaviour related to stunting. The results showed that digital media can be an effective means to increase knowledge about proper nutrition and a balanced diet, as well as invite active participation in sports activities and health monitoring. It can be concluded that digital media has great potential to improve people's healthy behaviour in preventing stunting. With the right approach and appropriate content development, digital media can be an effective tool in supporting nutrition education, the promotion of balanced diets, and healthy lifestyles broadly. Collaborative efforts between the government, health institutions, education, and the private sector are essential to maximise the positive impact of digital media utilisation in preventing stunting and reaching a healthier future generation